Rancang Bangun Aplikasi Augmented Reality Sebagai Media Promosi Kopi Pada Kedai Kopi Karmer Dengan Menggunakan Metode Maker Based Tracking - Windi Nelisa; Budi Apriyanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Coffee in one of the drinks which is the most preferred by various communities. Besides that, it also becomes a very profitable business. Many coffee companies in Indonesia compete in promoting their products. The rising of demand to the coffee business makes Kopi Karmer as the alternative to the problem in searching job or becomes business partner. Such as the business design which is offered by Kopi Karmer in the terms of product, cart of café. Kopi karmer is the new business coffee which uses the selection coffee from Sumatera, Aceh, and lampung using Augmented Reality which is based on Android. By the application of the Augmented Reality can give the ease in getting information and becomes the solution to choose Kopi Karmer as the alternative business which is in accordance with the need of consumer or business partner.